Preparation and physicochemical effects of zein nanofiber membrane encapsulated with citral/HP-β-CD inclusion complex and its application on cheese. (December 2022) - Shen, Chen; Chen, Wenqing; Li, Changzhu; Ye, Yong; Cui, Haiying; Lin, Lin
Abstract: As a nutritious cold chain food, cheese is susceptible to Listeria monocytogenes contamination. In order to prevent and control Listeria monocytogenes in cheese safely and efficiently, maintain the sensory quality during sale, this paper developed a novel nanofiber membrane with good mechanical strength, hydrophobicity, thermal stability, release performance and bacteriostatic performance as food active packaging. In this study, zein was introduced and electrospun to form a reliable carrier to embed and deliver citral in the cavity of HP-β-CD (Hydroxypropyl-β-cyclodextrin). We found that the zein-based nanofiber membranes showed preferable tensile properties and hydrophobicity with 4% (w:v) addition of citral/HP-β-CD inclusion complex. Meanwhile, the thermal stability and release property of citral were significantly improved by embedding in HP-β-CD and loading into zein-base nanofiber membranes. Moreover, after packaged by Zein nanofiber membrane encapsulated with citral/HP-β-CD inclusion complex under the storage conditions of 4 °C and 12 °C, the growth of Listeria monocytogenes in four kinds of cheeses was inhibited to a certain degree. The texture and sensory quality of the four cheeses at the two temperatures and the color quality under the low temperature condition of 4 °C did not change significantly. In summary, Zein nanofiber membranes encapsulated with citral/HP-β-CD inclusion complex has potential application prospects in the field of food active packaging. Graphical abstract: Image 1 Highlights: Cital/HP-β-CD inclusion complex was embedded in zein-based nanofibers successfully. Zein-based nanofibers possessed preferable tensile properties and thermal stability. The hydrophobicity of nanofibers was improved prominently after addition of zein. Sustainable release of citral in zein-based nanofibers was realized with the pore structure. The Zein-based nanofibers showed preferable preservation effects on cheese.